Respostas

A melhor resposta!
2014-05-02T23:44:49-03:00
f(x+3)=f(x)*f(3)

sabendo que f(3) = 2

f(x+3)=f(x)*2

como queremos saber o valor de f(x)
é só isolar
f(x+3)=f(x)*2\\\\ \frac{f(x+3)}{2} =f(x)

***************************************************************************************************
***************************************************************************************************
f(-3+3) = f(0)

calculando o valor de f(0)

 \frac{f(0+3)}{2} =f(0)\\\\ \frac{f(3)}{2} =f(0)

como f(3) = 2

 \frac{2}{2} =f(0)\\\\1=f(0)
**************************************************************************************************
***********************************************************************************************
agora f(-3)

 \frac{f(-3+3)}{2} =f(-3)\\\\ \frac{f(0)}{2} =f(-3)\\\\ \frac{1}{2} =f(-3)

\boxed{\boxed{f(-3)= \frac{1}{2} }}
3 5 3